Study on the impact of sudden stratosphere warming in the upper mesosphere-lower thermosphere regions using satellite and HF radar measurements - Mbatha, Nkanyiso; Sivakumar, Venkataraman; Malinga, Sandile B.; Bencherif, Hassan; Pillay, S. R. (Atmospheric Chemistry and Physics, 2010)
International audience The occurrence of a sudden stratospheric warming (SSW) excites disturbances in the mesosphere-lower thermospheric (MLT) wind and temperature. Here, we have examined the high frequency (HF) radar wind data from the South African National Antarctic Expedition, SANAE (72 S, 3 W), a radar which is part of the Super Dual Auroral Radar Network (SuperDARN). Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) on board the Thermosphere-Ionosphere-Mesosphere-Energetics and Dynamics (TIMED) satellite temperature data and National Centre for Environmental Prediction (NCEP) temperature and wind data are used to investigate the dynamical effects of the unprecedented September 2002 SSW in the Antarctica stratosphere and MLT. The mean zonal wind (from SANAE HF radar) at the MLT shows reversal approximately 7 days before the reversal at 10 hPa (from NCEP). This indicates that there was a downwards propagation of circulation disturbance. Westerly zonal winds dominate the winter MLT, but during the 2002 winter there are many periods of westward winds observed compared to other years. The normalised power spectrums of both meridional andzonal winds show presence of planetary waves (of 14-day period) before the occurrence of the SSW. The SABER vertical temperature profiles indicated the cooling of the MLT region before the SSW event.